ANALISIS TINGKAT LITERASI MEDIA MAHASISWA PENGHUNI KOS DI SEKITAR UNIVERSITAS NEGERI MEDAN - Natalia Dela Br Simamora; Melly Br Bangun; Christiana Junita; Febry Yanti (Journal Education for All: Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2025)
This study aims to analyze the level of media literacy among university students living in boarding houses around Universitas Negeri Medan (UNIMED). The research employed a quantitative descriptive method involving 50 respondents selected through a survey using a Likert-scale questionnaire that measured five indicators: the ability to distinguish factual information from hoaxes, habits of source verification, ethics in using social media, awareness of personal data security, and critical thinking in responding to digital content. The results show that students’ media literacy is generally in the good category, as reflected in their ability to access digital information easily, identify misleading content, use polite communication, and maintain privacy when using social media. However, some respondents still exhibit inconsistent verification habits and limited confidence in recognizing misinformation, indicating uneven literacy levels among students. These findings highlight the importance of strengthening digital awareness programs, especially for students living independently in boarding houses who rely heavily on online platforms for academic and daily information needs. The study suggests that universities develop continuous media literacy initiatives and that students cultivate more consistent verification habits to foster responsible digital behavior.